Structural-semantic features of vocabulary on the designation of dishes of the Ukrainian people in culinary books (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2018)
Thematic group of vocabulary on the designation of dishes is closely linked to the material culture of the people, which makes it possible to define it as a historical category and preserves information about the original folk culture, responds to socio-economic, cultural and historical changes in society. It is one of the oldest layers of Slavic vocabulary, which dates back to the Slavonic period, or even the Prido-European period. This allows us to investigate the patterns of formation and development of this group of vocabulary, to identify structural and semantic features, and others. The processes of occurrence of food, dishes and drinks, their formation and development, functioning in certain historical periods, their names were and are the subject of research of scientists of various branches of knowledge, in particular ethnologists, historians, sociologists, linguists, etc. Such intelligence is important for gastronomy: linguistic and culturological analysis form part of this “culinary” science. Equally important is the “culinary terminology” in scientific literature, in particular in recipes. A comparative analysis of culinary books, recipes books makes it possible to distinguish between common and excellent nominations that have structural and semantic peculiarities, their history of occurrence, and undergo certain changes. The book of recipes by S. Klinovetsky, one of the first Ukrainian culinary books, fully reveals the vocabulary group on the designation of dishes. According to the structural type, culinary terminology is represented by two groups: elementary (one / two-component) phrases and non-elemental (complex) three / four-component phrases. Among them, the most common are: noun-noun and noun-adjective (adjectival) phrases. The semantic nature of the nominations is motivated by the main component of the dish, the qualitative characteristic of the dishes (color, shape, texture, size, taste), the way of cooking, the purpose of another product / dish and ethnonim, which denotes the Ukrainian social color. At present, it is relevant to study the subject-thematic group of vocabulary on the designation of dishes and beverages, which is an element of the material and spiritual culture of the people.